2005
DOI: 10.2310/6350.2005.31235
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Human Fat for Soft Tissue Augmentation

Abstract: Viability of adipocytes frozen at -20 degrees C was very low when analyzed by staining, and no cultures could be established from any of the specimens. In contrast, viable adipocytes were recovered from samples that were controlled-rate frozen in the presence of cryoprotectants and stored in nitrogen vapor. CONCLUSION. Our results indicate that fat frozen at -20 degrees C is not viable and thus provides no advantage over inert fillers. The methods here described could readily be transferred to the clinical set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 19 publications
1
26
0
4
Order By: Relevance
“…79 In fact, cryopreservation of fat tissue is not a new research area and has been extensively investigated in large scale adipose tissue engineering, especially in applications of maxillofacial and craniofacial surgery. Although many studies found that freezing fat grafts by using optimal cryopreservation techniques enables their longterm preservation, [80][81][82][83][84][85][86] only few considered whether the frozen fat tissue could still be a reliable source of adult stem cells. 87,88 Further studies are required to determine whether cryopreserved fat tissue still maintains the viable and potent adult stem cells in quantities required for clinical needs.…”
Section: Clinical Banking Of Adipose Derived Adult Stem Cells (Ascs)mentioning
confidence: 99%
“…79 In fact, cryopreservation of fat tissue is not a new research area and has been extensively investigated in large scale adipose tissue engineering, especially in applications of maxillofacial and craniofacial surgery. Although many studies found that freezing fat grafts by using optimal cryopreservation techniques enables their longterm preservation, [80][81][82][83][84][85][86] only few considered whether the frozen fat tissue could still be a reliable source of adult stem cells. 87,88 Further studies are required to determine whether cryopreserved fat tissue still maintains the viable and potent adult stem cells in quantities required for clinical needs.…”
Section: Clinical Banking Of Adipose Derived Adult Stem Cells (Ascs)mentioning
confidence: 99%
“…Diferentes grupos de investigación han realizado trabajos que permiten obtener células madre de distintos tejidos humanos, como médula ósea y cordón umbilical (3)(4)(5)(6)(7)(8)(9). En nuestro estudio, hemos obtenido MSCs directamente del tejido graso aspirado mediante liposucción, siendo esta técnica mucho más sencilla y menos agresiva para el paciente que otros métodos (7), y que por lo tanto, puede ser fácilmente incluida como una técnica más de práctica habitual dentro de nuestra especialidad.…”
Section: Discussionunclassified
“…Además, estudiamos y analizamos la diferenciación de la célula madre proveniente de tejido graso hacia adiGráfico 1: Comparativa de marcadores en tejido graso fresco y congelado (6,(8)(9)(10) que para obtener la misma cantidad de células madre en 1gr. de tejido graso se necesitan 500 gr.…”
Section: Diferenciación Celularunclassified
See 2 more Smart Citations